Evaluation of Lambung Mangkurat University Student Academic Portal Using User Experience Questionnaires (UEQ) - Sari, Yuslena; Novitasari, Novitasari; Pratiwi, Hani (ILKOM Jurnal Ilmiah, 2021)
The student academic portal is one of the Academic Information Systems at Lambung Mangkurat University. The student academic portal can only be accessed by Lambung Mangkurat University students and can be used for academic guidance, managing student study plans, printing exam cards, filling out questionnaires, and viewing exam results (assessments). However, since its release in 2016, there has been no publication regarding evaluations on the website-based student academic portal. Evaluation is one of the stages in the Software Development Life Cycle (SDLC), this stage allows the user to provide an assessment of the system. This study aims to evaluate the student academic portal. Evaluation is carried out to determine user ratings of the existing system. The evaluation method used is the User Experience Questionnaire (UEQ). With this method, users can assess the ULM Student Academic Portal from various aspects, namely aspects of Novelty, Stimulation, Dependability, Efficiency, Perspicuity, and Attractiveness. The results of this study indicate that the Perspicuity aspect gets a high score while Novelty gets a low score.